Improving Antenatal Care (ANC) Focusing on Maternal Nutrition (MN) Services and Counseling Through Quality Improvement (QI) Approach in a Medical College Hospital in India. (29th May 2020) - Ghosh, Sebanti; Sharma, Praveen; Forissier, Thomas; Bhambri, Poonam
Abstract: Objectives: To demonstrate feasibility of applying Quality Improvement (QI) approach to improve maternal nutrition (MN) services and counseling during ANC provision at a state-run medical college hospital. Methods: Doctors and staff from the departments of Obstetrics & Gynaecology (OBGY), Pediatrics and Community Medicine in GSVM Medical College, Kanpur, Uttar Pradesh (a high case load facility) were trained on Point of Care Quality Improvement (POCQI) methodology developed by WHO, URC and All India Institute of Medical Sciences (AIIMS) by a team of QI experts engaged by Alive & Thrive (A&T). Thereafter, the OBGY department formed a QI team with the aim of improving MN component within the ANC services for pregnant women (PW). Specifically, QI aims to be achieved between May– Aug 2019 were set as: At least 80% of PW complete height, weight gain, blood pressure (BP) and hemoglobin (Hb) measurement and receive nutrition counselling, of which 70% can recall the MN nutrition messages imparted during the counselling session. Since no system for recording ANC data existed except Hb (50%), the baseline was set as zero for all other parameters. Post a system process review and problem analysis, 4 areas for improvement were identified: i) Streamlining patient flow; ii) ensuring timely availability of diagnostic reports to facilitate early detection of anemia; iii) recording and tracking of anthropometric data and, iv) provision of nutrition counselling to all PW. Simple and doable changes such as deployment of Red Cross volunteers for crowd management and patient flow, use of government-issued mother and child protection (MCP) cards for recording anthropometric data, engagement of HIV counselor for nutrition counselling etc. were applied with assistance and mentoring from QI experts. Results: 84% of the PW completed weight gain, Hb and BP measurement. MN counselling was delivered to 76% of the women. Exit interviews of PW to assess the comprehensiveness of the counselling provided show a steady improvement (∼12–15%) in retention of messages related to weight gain, importance of Ca and IFA, frequency of meals and diet diversity. Conclusions: It is feasible to improve MN services including counseling at ANC OPD in medical college hospital using QI approach, without additional resource investment. Funding Sources: The Bill & Melinda Gates Foundation.